Long-term renal outcomes in COVID-19 survivors: a cohort study - S. Naderi; K. Samadi; A. A. Zeraati; N. Mahdavifar; A. Kaffash; M. Akbari; Z. Jalambadani (Вестник урологии)
Introduction. COVID-19 has been associated with both acute and chronic extrapulmonary complications, including renal dysfunction. Understanding the long-term effects of COVID-19 on renal function is essential for managing recovery in affected individuals.Objective. This study aimed to evaluate the long-term renal outcomes in patients who recovered from COVID-19, focusing on changes in glomerular filtration rate (GFR), blood urea nitrogen (BUN), and serum creatinine levels in Iran.Materials & methods. A retrospective cohort study was conducted using data from the Mashhad University of Medical Sciences cohort. The study included patients who had confirmed COVID-19 and a minimum follow-up period of six months post-recovery. Renal function was assessed by measuring the Glomerular Filtration Rate (GFR), Blood Urea Nitrogen (BUN), and serum creatinine levels both at baseline (when COVID-19 was initially diagnosed) and at follow-up. Statistical analysis was performed to explore the associations between renal outcomes and various factors, including gender, the severity of COVID-19, and blood pressure status.Results. In the study, 55.3% were male, and the mean age of 51.38 ± 13.41. Among the patients, 55.3% were male and 44.7% were female. The difference in mean creatinine level between baseline and follow-up was significant (p < 0.001). The difference in mean GFR between baseline and follow-up was significant (p < 0.001). In men, the mean blood urea nitrogen at the first visit and at the follow-up difference was not statistically significant (p = 0.241). In women, the mean blood urea nitrogen was a statistically significant decrease (p = 0.003). Other parameters, including creatinine and GFR, did not differ significantly in both male and female groups at the time of hospitalization and follow-up.Conclusion. Overall, the results of this study suggest that COVID-19 can affect kidney function, especially in association with underlying factors such as hypertension and diabetes, and female gender, which may be risk factors for more severe renal complications in patients with COVID-19. The decrease in GFR in patients with hypertension and diabetes highlights the importance of controlling these diseases in patients with COVID-19. Overall, this study showed that COVID-19 can have lasting effects on patients' kidney function.